Tumour growth rate of carcinoma of the colon and rectum: retrospective cohort study. Issue 6 (30th September 2020) - Burke, J. R.; Brown, P.; Quyn, A.; Lambie, H.; Tolan, D.; Sagar, P.
Abstract : Background: The growth pattern of colorectal cancer is seldom investigated. This cohort study aimed to explore tumour growth rate in colorectal cancers managed non‐surgically or deemed not resectable, and to determine its implication for prognosis. Methods: Consecutive patients with colonic or rectal adenocarcinoma were identified through the colorectal multidisciplinary team database at Leeds Teaching Hospitals NHS Trust over a 2‐year interval. Patients who received no treatment (surgery, stenting, colonic defunctioning procedures, chemotherapy, radiotherapy) and who underwent CT twice more than 5 weeks apart were included. Multidetector CT/three‐dimensional image analysis was performed independently by three experienced radiologists. Results: Of 804 patients reviewed, 43 colorectal cancers were included in the final analysis. Median age at first CT was 80 (73–85) years and the median interval between scans was 150 (i.q.r. 72–471) days. An increase in T category was demonstrated in 31 of 43 tumours, with a median doubling time of 211 (112–404) days. The median percentage increase in tumour volume was 34·1 (13·3–53·9) per cent per 62 days. The all‐cause 3‐year mortality rate was 81 per cent (35 of 43) with a median survival time of 1·1 (0·4–2·2) years after the initial diagnostic scan. In those obstructed, the relative risk of death from subsequent perforation was 1·26 (95 per cent c.i. 1·07 to 1·49; P  = 0·005). Conclusion: This study documented a median doubling time of 211 days, with a concerning suggestion of tumour progression, which has implications for the current management standard. Abstract : Few studies have evaluated the growth pattern of colorectal cancer. Forty‐three patients who underwent CT twice more than 5 weeks apart were included over a 2‐year interval. The median doubling time was 211 days, with a concerning suggestion of tumour progression. This has implications both under the current 62‐day UK standard and following the rapid emergence of COVID‐19 and its global impact on surgical cancer care. Tumor volume changes in colorectal cancer Abstract : Antecedentes: El patrón de crecimiento del CRC ( colorectal cancer, CRC) ha sido poco investigado. El objetivo de este estudio de cohortes fue explorar la tasa de crecimiento tumoral en los pacientes con CRC no tratados quirúrgicamente o con tumores irresecables para determinar su valor pronóstico. Métodos: Los pacientes consecutivos con adenocarcinoma de colon o recto se identificaron a partir de la base de datos del equipo multidisciplinario colorrectal del "Leeds Teaching Hospitals NHS Trust" durante un período de 2 años. Se incluyeron los pacientes que no recibieron tratamiento (cirugía, colocación de endoprótesis, procedimientos de desfuncionalización del colon, quimioterapia, radioterapia), en los que se obtuvieron tomografías computarizadas con > 5 semanas de diferencia. El análisis de imágenes TC/3D multidetector fue realizado de forma independiente por tres radiólogos expertos. Resultados: De los 804 pacientes revisados, 43 CRCs se incluyeron en el análisis final con una mediana de 150 días (rango intercuartílico, interquartile range, IQR: 72‐471) entre los escáners. La mediana de edad en el primer escáner era de 80 años (IQR: 73‐85). En 31 (72%) casos, se demostró un aumento del estadio TNM del tumor, con un tiempo medio de duplicación del tamaño tumoral de 211 días (IQR: 112‐404). La mediana de aumento porcentual del volumen del tumor era de un 34% cada 62 días (IQR: 13, 3‐53, 9). La mortalidad por cualquier causa a los 3 años fue del 81% (35/43), con una mediana de supervivencia de 1, 1 años (IQR: 0, 4‐2, 2) desde el escáner inicial diagnóstico. El riesgo relativo de mortalidad como resultado de la obstrucción intestinal y perforación subsiguiente era de 1, 26 (i.c. del 95% 1, 07‐1, 49, P < 0, 01). Conclusión: Este estudio documentó una mediana de tiempo de duplicación del tamaño del tumor de 211 días, así como datos preocupantes de la progresión del tumor que podrían tener repercusión en el tratamiento estándar actual.